(untitled) - Lyons, Nick (New York, 1976)
Describes Sony's pioneering marketing and management techniques and the unique product development that have made it a major multinational firm.
Keywords: Công nghiệp điện tử,Electronic industries; Lịch sử,History; Nhật Bản,Japan